Penggunaan Asap Cair Tempurung Kelapa untuk Menurunkan Kadar Timbal (Pb) pada Biji Kedelai (Glycine max) - Sri Hartati; Purnama Darmadji; Yudi Pranoto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2015)
Liquid smoke of coconut shell has functional properties as bioflavor, preservative, and chelating agent, because it contains the active compounds of phenol, carbonyl, and acid. But the use of liquid smoke as chelating agent had not been developed. A study on chelation of heavy metal Pb by coconut shell liquid smoke on soybean seeds has been conducted. The aimed of the study was to evaluate the effectiveness of liquid smoke in the reducing heavy metals Pb in soybean seeds, evaluate the change in the components of the liquid smoke was used for chelation heavy metals Pb, and evaluate the influence of the phenol, carbonyl, and acid components in the chelation heavy metals Pb in soybean seeds. Liquid smoke of coconut shell pyrolysis has a specific gravity of 1.01 g/ml, pH 1.81, phenol 1.20%, carbonyl 5.75%, and acid compounds 8.40%. Soybean seeds soaked in coconut shell liquid smoke with various concentration of 0% (control/aquademineralisa); 12.5%; 25%; 50%; and 100% for 2 hours. Levels of heavy metals Pb was analyzed by Atomic Absorption Spectrophotometer. The changes of liquid smoke compounds such as pH, specific gravity, phenol, carbonyl, and acid was analyzed. The influence of the components of liquid smoke to the reduction of the heavy metals Pb was also analyzed. Model experiment was made from soybean seeds that have been contaminated by Pb (NO standard solutions with a concentration of 2 ppm. The results showed the higher the concentration of liquid smoke is used for soaking the decreased levels of heavy metals Pb is also getting bigger. The liquid smoke 100% (without 3)2dilution) gives the best reducing effect that can reduce heavy metal Pb 63.41%. An increase inpH, a decrease in phenol levels, decreased levels of the carbonyl, and decreased levels of the acid inliquid smokethat used for soaking indicatesthat the component has been successfully chelated the heavy metals Pb in soybean seeds.The phenol components of liquid smoke give the highest reducing effect 50.09%, followed by acid compounds 45.67%, and carbonyl compounds 42.21%.ABSTRAKTelah dilakukan penelitian tentang khelasi logam berat Pb pada biji kedelai dengan menggunakan asap cair tempurung kelapa. Tujuan penelitian adalah untuk evaluasi efektivitas asap cair dalam menurunkan kadar logam berat Pb pada biji kedelai, evaluasi perubahan komponen penyusun asap cair setelah digunakan untuk khelasi logam berat Pb, dan evaluasi pengaruh dari komponen penyusun asap cair dalam menurunkan kadar logam Pb pada biji kedelai. Biji kedelai direndam dalam asap cair tempurung kelapa dengan variasi konsentrasi 0% (kontrol atau aquademineralisa); 12,5%; 25%; 50%; dan 100% selama 2 jam. Parameter yang diamati adalah penurunan kadar Pb pada biji kedelai, perubahan pH, senyawa fenol, karbonil, dan asam yang terdapat dalam asap cair setelah proses khelasi, dan pengaruh komponen senyawa fenol, karbonil, dan asam terhadap penurunan kadar logam Pb pada biji kedelai. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan tiga kali ulangan. Model percobaan dibuat dengan biji kedelai yang dicemari larutan Pb(NO3)konsentrasi 2 ppm. Hasil penelitian menunjukkan bahwa semakin tinggi konsentrasi asap cair yang digunakan untuk perendaman maka penurunan kadar logam berat Pb juga semakin besar. Asap cair dengan konsentrasi 100% (tanpa pengenceran) memberikan efek penurunan kadar logam berat Pb yang paling baik yaitu sebesar 63,41%. Adanya kenaikan pH, penurunan kadar fenol, penurunan karbonil, dan penurunan kadar asam pada asap cair yang telahdigunakan untuk perendaman menunjukkan bahwa komponen asap cair tersebut telah berhasil mengkhelat logam Pb pada biji kedelai. Komponen senyawa fenol memberikan efek penurunan kadar Pb yang paling tinggi yaitu 50,09%, diikuti oleh komponen asamsebesar 45,67%, dan komponen karbonil sebesar 42,21%.